(untitled) (Minerva, 2019)
It has been generally accepted until today that there are many thematic and linguistic coincidences between ancient Greek romances and Apocryphal Acts of the Apostles; it is a very dangerous affirmation without an exhaustive analysis of the texts. With this paper, whose first part is devoted to phonetics and morphology, we try to fill a gap in the study of Acta Pauli and Acta Petri. We do this from a linguistic point of view, comparing those texts with Xenophon’s Έφεσιακά after Mann’s work, in order to modernize it. We can see some parallelisms relating to contents, but not to language.